MANAGEMENT, ORGANISATION AND CHILDBIRTH towards a new model for the birth path. - Piscopo, Gabriella; Ruberto, Margherita ([S.l.] : ROUTLEDGE, 2022)
Management, Organization and Childbirth: Towards a New Model for the Birth Path explores the complex topic of the birth path with a multidisciplinary magnifying glass on the paradigms, languages, and tools critical to the organization, management, and clinical science. The work consists of five chapters. The first chapter provides a multidimensional analysis of childbirth. The second chapter presents an organizational analysis that moves in unison with different models of health. The third chapter studies the birth path in organizational and cynical terms by describing it in its core processes. The fourth chapter proposes a study conducted in the Italian context, which identifies some useful determinants for redesigning the birth path. The fifth chapter formulates a proposal for redesigning the birth path based on a new health paradigm. The proposed model offers useful insights for multiple categories of readers. To students of medicine and higher education tracks in healthcare management, it can offer opportunities to raise awareness not only regarding multi-professional practice but also regarding confrontation with complementary disciplines. To practitioners and policy makers, it can provide useful stimuli to promote rational and informed decisions around the childbirth. To researchers studying the health context within different disciplinary domains, the model can offer unexplored research spaces within the new business complex system.
OCLC-licensed vendor bibliographic record.
Keywords: Maternal health services; Childbirth; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Organizational Behavior